IDENTIFIKASI PEMBELAJARAN BERDIFERENSIASI DALAM MATA PELAJARAN BAHASA INDONESIA - Djamun, Tirtayasa; Sabarua, Jefrey Oxianus; Suoth, Like (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to identify the implementation of differentiated instruction in the Indonesian language subject for Grade V at SD Inpres Wari Tobelo and to analyze its impact on students’ language skills. The research problem focuses on two main aspects: the strategies used in implementing differentiated instruction and its impact on students’ language skills. The research method employed is a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The data analysis technique involves several stages, including data reduction, data presentation, and conclusion drawing. The results of the study show that: Differentiated instruction strategies are implemented through mapping students’ learning readiness, interests, and learning profiles. The teacher adjusts the content, process, and product of learning according to students’ needs. There is a positive impact on students’ listening, speaking, reading, and writing skills, as each student feels valued and motivated according to their learning style. The main challenges in implementation include limited learning facilities, a lack of teacher understanding of the